S1, a Novel Pan-BH3 Mimetic, Induces Apoptosis in Mcl-1-Overexpressing Cells Through Bak - Ting Song; Xilong Chang; Zhichao Zhang; Yubo Liu; Xiaoyun Shen (Elsevier, 2012)
Mcl-1, an anti-apoptotic Bcl-2 homolog that has a structurally divergent BH3-binding pocket, non-redundant action model, and unique characteristic of short life confers complete resistance to the BH3 mimetic ABT-737. Herein, we used S1, previously identified as a Mcl-1/Bcl-2 dual inhibitor and a pure BH3 mimetic, to explore the mechanism of Mcl-1's action and supply a strategy to challenge Mcl-1's protection. Apoptosis assay in SMMC-7721, HCT116, and K562 cells demonstrated that S1 can effectively challenge Mcl-1's anti-apoptotic effect. Notably, we discovered an unexpected dynamic change of Mcl-1 that directly correlates with resistance or commitment to apoptosis induced by both ABT-737 and S1. Co-immunoprecipitation assays demonstrated that Mcl-1 increase results from Bim trafficking from Bcl-2 to Mcl-1, while subsequent Bak released by S1 determines Mcl-1 decrease and full-blown apoptosis. Further experiments using Bak shRNA testified that Bak accounts for S1-induced apoptosis and Mcl-1 decrease. Consistently, Bax-deficient DU145 cells are sensitive to S1, whereas Bak-mutant MKN-28 cells are significantly more resistant. The in vitro model could be extended to an in vivo mouse xenograft model in which Mcl-1 confers resistance by increased protein level, and the release of Bak could serve as a biomarker of apoptosis.[Supplementary materials: available only at http://dx.doi.org/10.1254/jphs.12103FP] Keywords:: BH3 mimetic, Bcl-2/Mcl-1 dual inhibitor, Mcl-1 dynamics, Bax, Bak